2016
DOI: 10.1016/j.jclinepi.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing minimally disruptive medicine: disruption from illness and health care-related demands is correlated with patient capacity

Abstract: Our sample generally had capacity comparable to other populations and may be able to meet the demands imposed by treatment. Those with reduced physical, financial, and mental capacity reported higher disruption and represent a vulnerable group that may benefit from innovations in minimally disruptive medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Finally, our novel sub-focus on the relationship between health coaching and patient capacity will elucidate any basis to the hypothesis that we can enhance health in chronic conditions by focusing on developing a sub-category of coaching, deemed “Capacity Coaching.” This is in line with the extensive body of research growing to support the practice of Minimally Disruptive Medicine [1315, 3032], of which Capacity Coaching would be a component. Finally, to make it easier to design and implement effective health coaching interventions in support of the 66 % of Americans with chronic conditions, this review seeks to identify key characteristics of successful coaching interventions.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Finally, our novel sub-focus on the relationship between health coaching and patient capacity will elucidate any basis to the hypothesis that we can enhance health in chronic conditions by focusing on developing a sub-category of coaching, deemed “Capacity Coaching.” This is in line with the extensive body of research growing to support the practice of Minimally Disruptive Medicine [1315, 3032], of which Capacity Coaching would be a component. Finally, to make it easier to design and implement effective health coaching interventions in support of the 66 % of Americans with chronic conditions, this review seeks to identify key characteristics of successful coaching interventions.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, patients draw on capacity to make adaptations over time to overcome treatment burden associated with chronic conditions [14]. Studies that have examined capacity have shown that patients most disrupted by treatment had serious limitations to their physical, emotional, and financial capacities [15] while care plans that attended to patient capacity were more effective in reducing 30-day hospital readmissions [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Impact refers to a patient's perception of the effect of the workload on role, social, physical, and psychological functioning. Financial challenges, confusion about medical information, and challenges with the healthcare system may add to the weight of the burden that is felt by the patient [2-6]. High treatment burden is an important clinical issue as evidence suggests that it may negatively affect behavioral and clinical outcomes such as adherence [7-11].…”
Section: Introductionmentioning
confidence: 99%
“…Still, patients may be able to draw upon available capacity in some domains in order to overcome limitations in others. They may also report surprisingly low disruption from illness and treatment despite high levels of healthcare work [3]. This suggests a dynamic relationship between elements of patients’ capacity that makes it on the whole difficult to define, measure, or discuss in clinical practice.…”
Section: Introductionmentioning
confidence: 99%